Influencia del programa de cuentos mágicos en la producción de textos narrativos en las niñas del cuarto grado de educación primaria de la Institución Educativa Nº 81007 Modelo - Trujillo, 2016 - Rodríguez Angeles, Lucero Stefany (2019)
The research work is titled Influence of the Magic Stories Program in the production of narrative texts in the girls of the fourth grade of primary of the I.E Nº 81007 "Modelo" - Trujillo, 2016. The general objective is to determine the influence of the application of the program combining magic stories in the improvement of the production of written texts in the girls of the 4th grade of Primary Education of the I.E. "Modelo" Nº 81007 of the city of Trujillo 2016. We worked with a sample consisting of section A and C each with 25 students from the fourth grade who were chosen at random. We used as a quasi experimental research design with the experimental group being the "A" section and the control group the section "C" with pre and post test. At the conclusion of the research, after applying the magic story program in the experimental group, the results show that there was a significant improvement in the production of texts.